Numerical analysis on hydrogen swirl combustion and flow characteristics of a micro gas turbine combustor with axial air/fuel staged technology. (25th January 2023) - Liu, Hong; Zeng, Zhuoxiong; Guo, Kaifang
Highlights: Axial air staging, axial fuel staging and jet stabilized technology are combined with swirl combustion. Outlet NO emission decreases from 20.2 ppm to 2.28 ppm as secondary air ratio grows from 0 % to 40 %. Fuel staging has a more significant effect on reducing NO emission than air staging. Abstract: To analyze the effects of the two staging techniques on combustion characteristics and emissions, the influence of different secondary oxygen ratios (0–40 %) and secondary fuel ratios (0–10 %) on the combustion flow, emission characteristics, field synergy and other parameters of the micro gas turbine combustor are investigated by numerical simulation based on computational fluid dynamics (CFD) method. The realizable k-epsilon model is adopted for turbulence simulation, the combustion model is general finite rate model. The results show that with the increase of secondary oxygen ratio from 0 % to 40 %, scope of central recirculation zone becomes smaller, outlet velocity grows, OTDF becomes larger and pressure loss rises, the average outlet NO emission decreases from 20.2 ppm to 2.28 ppm, synergy angle β of the central plane becomes larger, and the change mainly occurs in the recirculation zone and the rear of the combustion chamber. As the secondary fuel ratio grows, outlet velocity decreases, pressure loss drops, and the outlet temperature distribution becomes more and more uniform. The synergy between velocity and temperature gradient of the central plane becomes better. When the secondary fuel ratio is 10 %, the maximum NO emission on the central axis is 9.27 ppm, which is only 8.51 % of the fuel unstaged value. The outlet NO emission does not drop monotonously with more secondary fuel. Fuel staging has a more significant effect on reducing NO emission than air staging.